Histological study of the influence of antidiabetic plant collection on pancreatic tissue in rats with diabetes mellitus, which is induced by dexamethasone - A. O. Savych; S. M. Marchyshyn; N. M. Ostrovsky; Y. B. Laryanovska (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Diabetes mellitus is a global problem today, because there is a sharp increase the number of patients in the world each year. Severe complications of diabetes are very dangerous because it can lead to disability of patients and high mortality. The aim of our work was to study the protective effect of antidiabetic plant collection on the pancreas in rats with diabetes type 2, caused by the introduction of dexamethasone. The research materials were pancreatic tissue of rats with experimental diabetes that received the decoction (1:10) of antidiabetic plant collection (witch includes Equiseti arvensis herba, Sambuci flores, Inulae rhizomata et radices, Hyperici herba, Tiliae flores, Polygoni avicularis herba, Myrtilli folium, Urticae folia) in treatment and preventive mode. The model of diabetes mellitus was induced by administration of dexamethasone 0.125 ml/kg for 15 days. Decoction of antidiabetic plant collection in doses 6 ml/kg, 9 ml/kg and 12 ml/kg reduces diabetogenic properties of dexamethasone when administered simultaneously. The insular tissue increases absorbance pancreatic islets, to some extent restored the normal percentage distribution of the islets in size, histologically visualized the increase more high-grade cells. The study found that antidiabetic plant collection reduces destructive-dystrophic changes of insular apparatus in rats with diabetes type 2. Antidiabetic effect of the studied plant collection has dose-dependent nature. The most effective conditional-effective doses are 9 and 12 ml/kg.